2019
DOI: 10.1038/s41380-019-0464-7
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and replication of cerebral blood flow differences in major depressive disorder

Abstract: Major depressive disorder (MDD) is a serious, heterogeneous disorder accompanied by brain-related changes, many of which are still to be discovered or refined. Arterial spin labeling (ASL) is a neuroimaging technique used to measure cerebral blood flow (CBF; perfusion) to understand brain function and detect differences among groups. CBF differences have been detected in MDD, and may reveal biosignatures of disease-state. The current work aimed to discover and replicate differences in CBF between MDD participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 38 publications
4
14
0
Order By: Relevance
“…Although the cognitive impairment was also associated with the insular atrophy, a significant correlation between the insula and depressive symptoms was observed after excluding the effect of the cognitive impairment. The result strongly indicated that the insula is vital in the modulation of emotion, which is consistent with previous research that demonstrated insular structures to be abnormal in patients with depressive disorder (Hayata et al, 2015;Ambrosi et al, 2017;Cooper et al, 2019;Whitton et al, 2019;Xu et al, 2019). The insula, as a vital visceral sensory node, is significantly correlated with somatic symptoms in depressed patients (Zu et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Although the cognitive impairment was also associated with the insular atrophy, a significant correlation between the insula and depressive symptoms was observed after excluding the effect of the cognitive impairment. The result strongly indicated that the insula is vital in the modulation of emotion, which is consistent with previous research that demonstrated insular structures to be abnormal in patients with depressive disorder (Hayata et al, 2015;Ambrosi et al, 2017;Cooper et al, 2019;Whitton et al, 2019;Xu et al, 2019). The insula, as a vital visceral sensory node, is significantly correlated with somatic symptoms in depressed patients (Zu et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Our study included moderate dementia with MMSE of about 14 and mild depression with mean HAMD of 13.11, which were different from those studies using SPECT and PET including mild dementia with MMSE ranging from 21 to 24 ( 5 , 6 , 23 , 24 ). Hyperperfusion in the supramarginal gyrus was also observed in AD patients with depression, which could be supported by findings of the increased CBF in the right supramarginal gyrus in patients with major depressive disorder ( 26 , 27 ) and depression in AD ( 1 ). Emotion regulation can cause neurons to activate in the regional brain ( 25 ).…”
Section: Discussionsupporting
confidence: 65%
“…Due to its quantitative and noninvasive nature, ASL has become a popular approach for studying cerebral hemodynamics in health and also in a range of cerebrovascular ( Donahue et al, 2017 ; Wang et al, 2020 ; Bastos-Leite et al, 2008 ; van Dalen et al, 2016 ; Bahrani et al, 2017 ), neurodegenerative ( Thomas et al, 2019 ; Dolui et al, 2020 ), and psychiatric disorders ( Cooper et al, 2019 ). This rise in popularity over the past decade led to the release of a consensus statement from the Perfusion Study Group of the International Society on Magnetic Resonance in Medicine, which provided guidelines for acquisition and processing of ASL data for clinical use ( Alsop et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%